Set her free: A creative nonfiction anthology on female pleasures - Cruz, Beatriz Marie D. (Animo Repository, 2022)
Sexuality is an aspect of one’s self that fundamentally impacts feelings, thoughts and behavior. Beyond reproduction, it conveys attraction to other people and shapes humans as primal, pleasure-seeking beings. Despite sexual instinct being innate, there exists a dominant, negative conception of sex and pleasure that profoundly affects people’s lives in some societies. This particular study explores the sexual desires, pleasures and urges that young Filipino women hold, and the reasons why they continue to harbor fear and guilt at the prospect of exploring these feelings. Such reasons comprise societal influences like family, school, religion, relationships, and culture. The researchers of this study uncover how and to what extent these affect a woman’s sexual behavior. The thesis yielded a web magazine (“webzine”) containing three creative nonfiction articles. With accompanying visuals, the articles chronicle a series of sexual experiences from three Filipino women. Through its anthological, narrative-like yet informative approach, unique stories that encompass masturbation, sexually explicit fanfiction and the loss of one’s virginity shall convey relatability to its readers and normalize explorations of female sex and pleasure. In spite of stigma surrounding the subject matter, such explorations are forms of self-love and lessons that promote body ownership.